College Students Sport Orientation After Following Basketball Sport Education - Fauzan Effendy; Riki Ramadhan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study aims to examine the difference in the influence between SE teaching and conventional teaching on student sports orientation using basketball. The research method in this study uses experiment with the randomized pretest-posttest control group design. The participants were 48 students of the PJKR study program at STKIP Nahdlatul Ulama Indramayu. The research instrument uses Sport Orientation Questionnaire for students majoring in sports. The research data were analyzed using independent samples t-test. The results of the study concluded that there were differences in the influence between SE teaching and conventional teaching on student sports orientation using basketball. In order to carry out further research using other sports besides basketball and to conduct further investigations at the end of season tournament using SE.